Connecting people with their communities through proximity‐based digital storytelling. Issue 1 (24th October 2017) - Detlor, Brian; Nosrati, Fariba; Crippa, Claudia
ABSTRACT: This visual presentation describes the results of a library‐led initiative involving the use of iBeacon proximity‐based technologies to connect people with their communities. The two libraries involved in this initiative developed and tested an app that pushed community‐based digital stories to users' smartphones and tablets when users were physically near a historic or cultural object (e.g., statue, landmark) about which the digital story was based. Using proximity‐based technologies to deliver stories about cultural and historic objects of interest to a community was thought to be a novel and engaging way to rally emotional connection and pride in one's own community. To test this hypothesis, as well as the viability of using iBeacon technology as a storytelling delivery mechanism, a pilot study was conducted with 50 participants from the general public at the two libraries involved in the initiative. Participants used the app to browse and read stories pertaining to a prominent park in the city. Posters with pictures of historic or cultural objects within the park were installed throughout each library. Each poster was enabled with iBeacon technology so that digital stories about the historic or cultural object displayed on the poster were automatically pushed to participants' smart devices as participants became near. To collect data on users' experiences and satisfaction with the app and the digital stories, on‐the‐spot interviews were conducted with participants after they finished visiting the posters and reading the digital stories. Interview data were analyzed using content data analysis techniques. A Likert‐scaled questionnaire was also administered; this data was analyzed using factor analysis and hierarchical regression. Results suggest that proximity‐based digital storytelling is a viable approach to connect people with their communities, especially if the stories provide people with relevant, timely, location‐based community information that stirs a positive emotional response.